2015
DOI: 10.4254/wjh.v7.i28.2829
|View full text |Cite
|
Sign up to set email alerts
|

Update on hepatitis C: Direct-acting antivirals

Abstract: Hepatitis C virus (HCV) was discovered 26 years ago. For decades, interferon-based therapy has been the mainstay of treatment for HCV. Recently, several direct-acting antivirals (DAAs) have been approved for treatment of HCV-infected patients and to help combat the virus. These drugs have revolutionized the management of HCV as all-oral regimens with favorable side effect profiles and superior rates of sustained virological response. Emerging real-world data are demonstrating results comparable to registration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Since the release of the first generation DAA's in 2011 there has been an explosion in the number and combination of DAA's available. Clinical trials have consistently reported SVR 12 rates >95% for most patient populations, including those patients co-infected with HIV, which have been supported by recent real world data (12)(13)(14). Treatment guidelines maintained as a living document online by the collaboration of American Association for the Study of Liver Disease (AASLD) and the Infectious Diseases Society of America (IDSA) are rapidly changing, however all oral DAA therapy is now the standard of care for all patient populations (15).…”
supporting
confidence: 54%
“…Since the release of the first generation DAA's in 2011 there has been an explosion in the number and combination of DAA's available. Clinical trials have consistently reported SVR 12 rates >95% for most patient populations, including those patients co-infected with HIV, which have been supported by recent real world data (12)(13)(14). Treatment guidelines maintained as a living document online by the collaboration of American Association for the Study of Liver Disease (AASLD) and the Infectious Diseases Society of America (IDSA) are rapidly changing, however all oral DAA therapy is now the standard of care for all patient populations (15).…”
supporting
confidence: 54%
“…The standard-of-care therapy against HCV consists of pegylated alpha interferon (peg-IFN-␣) and ribavirin, which can cure approximately 50% of HCV-infected patients. Direct-acting antivirals (DAAs) have recently been used and have increased the cure rate to about 90% (3). Therefore, the development of an HCV vaccine and the identification of host factors for new anti-HCV targets remain significant challenges.…”
mentioning
confidence: 99%
“…Ombitasvir is approved for treatment of genotype 1 in combination with paritaprevir, ritonavir, and dasabuvir. Ledipasvir is approved for genotypes 1, 3, and 4 in combination with sofosbuvir +/− RBV [20]. Velpatasvir in combination with sofosbuvir was approved in June 2016 by the FDA and became the first regimen approved for genotypes 1-6 [21].…”
Section: Ns5a Inhibitorsmentioning
confidence: 99%